The UbuWeb Electronic Music Corpus: An MIR investigation of a historical database. Issue 1 (5th March 2015) - Collins, Nick
<x content-type="archive" xml:space="preserve">Abstract</x> A corpus of historical electronic art music is available online from the UbuWeb art resource site. Though the corpus has some flaws in its historical and cultural coverage (not least of which is an over-abundance of male composers), it provides an interesting test ground for automated electronic music analysis, and one which is available to other researchers for reproducible work. We deploy open source tools for music information retrieval; the code from this project is made freely available under the GNU GPL 3 for others to explore. Key findings include the contrasting performance of single summary statistics for works versus time series models, visualisations of trends over chronological time in audio features, the difficulty of predicting which year a given piece is from, and further illumination of the possibilities and challenges of automated music analysis.